Strategi Komunikasi Organisasi Ketua Karang Taruna Sub Unit 032 Kecamatan Jatiasih dalam Meningkatkan Loyalitas Anggota - Avriliani Sugianto; Murtiadi Murtiadi; Roynaldi Arista (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
This study aims to identify, describe, and analyze the organizational communication strategy implemented by the Chairman of the Youth Organization Sub Unit 032 of Jatiasih District in increasing member loyalty. The phenomenon behind this study is the fluctuation in the presence of members in organizational activities and the challenge of maintaining active youth participation in the digital era. Members' loyalty is seen as a determining factor for the success of an organization in carrying out social, cultural, and community programs. The research method used is qualitative with a descriptive approach. Data was collected through in-depth interviews, direct observation of Karang Taruna activities, and documentation of organizational archives. The research informants were selected using purposive sampling techniques, including the Chairman of the Youth Organization and members who actively participated. Data analysis is carried out using an interactive model that includes collection, reduction, data presentation, and conclusion drawn. The results of the study show that the communication strategy of the Chairman of the Youth Organization is democratic, participatory, and interpersonal. The communication media used is in the form of WhatsApp Groups for quick coordination and face-to-face meetings to strengthen emotional bonds between members. The Chair also utilizes informal strategies such as casual conversations and non-formal social interactions to get closer to members. This strategy has a positive effect on member loyalty indicators, such as compliance, responsibility, active participation, and a sense of belonging to the organization. This study concludes that effective, open, empathetic, and adaptive communication to the needs of members is the main factor in strengthening the loyalty of youth organizations. These findings are expected to make an academic contribution to the study of community-based organizational communication and practical benefits for Karang Taruna administrators and similar organizations in managing membership dynamics at the local level.